R IMPLEMENTASI KEGIATAN OUTING CLASS UNTUK PENGENALAN NAMA BENDA HURUF L MELALUI MEDIA GAMBAR DI KELAS 1 SEKOLAH DASAR: Implementasi Outing Class dalam Pengenalan Nama Benda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine students’ responses to the introduction of object names beginning with the letter “L” using images in Outing Class activities and to identify the types of objects that can be introduced to firs grade students. For first grade students, learning object names is important for language development. Outing Class offers a fun, experience based learning method. Pictures were chosen to support Outing Class because they can provide clear and attractive visualizations, especially for objects that are difficult to find, making it easier for students to recognize and remember objects. The methodology used in this study was descriptive qualitative with data collection through observation and interviews. This study involved one teacher and 26 first grade students at SD Muhammadiyah 1 Gresik as subjects. The conclusion of the study shows that the image media used in the Outing Class is affective in improving the recognition of the names of objects that begin with the letter “L”. Tis media successfully introduced various object such as lamps, floors, and drawers. The students responses showed high enthusiasm. A total of 22 students stated that the pictures and Outing Class activities helped them recognize objects and their functions. In addition to helping them recognize objects, this method also increased student engagement and had a positive impact on their language development.